2016
DOI: 10.1017/s1049023x16000327
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Crush Syndrome through Aggressive Early Resuscitation: Clinical Case in a Buried Worker

Abstract: Aggressive early management with isotonic solutions before hospital arrival is an effective option for nephron-protection and prevention of crush syndrome. Mardones A , Arellano P , Rojas C , Gutierrez R , Oliver N , Borgna V . Prevention of crush syndrome through aggressive early resuscitation: clinical case in a buried worker. Prehosp Disaster Med. 2016;31(3):340-342.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
(23 reference statements)
0
5
0
1
Order By: Relevance
“…Patients who developed AKI in our study had serum CK levels above 3000 U/L ( 14 ). Regardless the cause, the treatment of rhabdomyolysis is identical, and the treatment goals are directed towards maintaining adequate tissue perfusion and oxygenation, thus preventing hypo perfusion and hypoxia, eliminating the products of rhabdomyolysis and maintaining urine output, preventing acute kidney injury, as well as eliminating the primary cause of rhabdomyolysis ( 2 , 3 , 10 , 15 ). Main goal of the treatment is to prevent acute kidney failure by maintaining urine output of 200-300 ml/hour ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who developed AKI in our study had serum CK levels above 3000 U/L ( 14 ). Regardless the cause, the treatment of rhabdomyolysis is identical, and the treatment goals are directed towards maintaining adequate tissue perfusion and oxygenation, thus preventing hypo perfusion and hypoxia, eliminating the products of rhabdomyolysis and maintaining urine output, preventing acute kidney injury, as well as eliminating the primary cause of rhabdomyolysis ( 2 , 3 , 10 , 15 ). Main goal of the treatment is to prevent acute kidney failure by maintaining urine output of 200-300 ml/hour ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Main goal of the treatment is to prevent acute kidney failure by maintaining urine output of 200-300 ml/hour ( 3 ). It is suggested to initiate aggressive fluid resuscitation by using normal saline, and to avoid potassium and lactate rich solutions because of the increased risk of hyperkalemia and lactate acidosis that accompany rhabdomyolysis ( 2 , 3 , 15 ). Diuretics are recommended, as well as alkalization of urine by adding sodium bicarbonate into normal saline solutions in order to decrease the cast formation and minimize the toxic effect of myoglobin on the renal tubules.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 37 references included in the PHLSDC data extraction, the subthemes more frequently identified were the collection of the mechanism of injury ( n = 13) and exposure to environment time ( n = 12), the importance of stopping the bleeding maneuvers ( n = 11) and PH fluid resuscitation ( n = 14), basic and advanced monitoring to guide PHLSDC interventions, including cardiac monitoring ( n = 9), pulse oximetry ( n = 6), and physiological monitoring ( n = 7), re-assessment of MCI casualties through continuous vital signs monitoring ( n = 8) and treatment of casualties according to triage prioritization ( n = 13). Furthermore, the authors identified the following “hot” issues worthy of further attention: PH management of crush syndrome [ 75 ], resuscitation of avalanche victims [ 53 , 54 ], and shared CBRNE treatment protocols [ 60 , 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…References from the PHLSDC scoping review highlighted the need to focus on assessment and treatment guidelines for crush injuries during MCIs [ 46 , 63 , 75 ], as well as for the development of awareness on chemical, biological, radiological, nuclear, and explosive (CRBNE) events, advocating for education, training, and competencies to be developed across all agencies [ 48 , 57 , 71 , 76 , 79 , 81 ]. Similarly, control of major hemorrhages as an integral part of the triage process emerged as a recurrent topic in the included PHLSDC references, with a special emphasis on the role of non-medical bystanders, as specifically stressed by the Hartford Consensus after the Sandy Hook Elementary School mass shooting and by Lesaffre and colleagues after the 2015 Paris attacks [ 46 48 , 50 , 51 , 61 63 , 73 , 77 , 80 , 169 ].…”
Section: Discussionmentioning
confidence: 99%
“…До евакуації з-під завалу починайте інфузію кристалоїдів (0,9% розчин натрію хлориду) зі швидкістю 1000 мл/год (10-15 мл/кг/год). Агресивне раннє лікування ізотонічними розчинами до госпі-Emergency Medicine (Ukraine), ISSN 2224-0586 (print), ISSN 2307-1230 (online) Лікарю, що практикує / Practicing Physician талізації є ефективним варіантом захисту нефронів і профілактики синдрому тривалого стискання тканин [6]. Пацієнти, як правило, переживають вивільнення, якщо інтенсивне лікування й моніторинг розпочаті, доки пацієнт ще залишався в пастці [7].…”
Section: Nb! чим раніше будуть проведені лікувальні заходи тим вищою ...unclassified